Cross-Sessional Study of Digital Advertising and Consumer Purchasing Behaviour in Delta State - Ijeh, Patrick Nkemdilim; Ivwighren, Hannah Emuobosa; Uwayah, Lydia I. (PERSPEKTIF, 2024)
This study investigated the link between digital advertising and consumer purchasing behavior in Delta State. This study recognized the prevalence of digital advertising and how advertising generally influences consumer purchasing behavior. However, this study focused on the channels of digital advertising available in Delta state, the patterns of consumer purchasing behavior among the study population, and examined how the usage of smart gadgets increases consumers’ access to digital content. The study relied on Technological Determinism as a theoretical framework and adopted the survey method in a cross-sectional research design. A sample of 400 was chosen for the study based on the Taro Yamane formula while respondents were selected purposively based on their knowledge of the subject matter. The study used a structured questionnaire to collect data, and the answers were presented using the mean outcome of the descriptive statistics. The hypotheses were tested using Analysis of Variance (ANOVA) statistics using Stata 15.0 software. Findings show that channels of digital advertising such as email advertising, social media, and pop-ups are acknowledged to be creating more visibility of products to consumers. The study affirms the usage of smart gadgets to create an easy avenue for consumers' purchasing behavior to flourish. The study recommends that channels of digital advertising such as email advertising, social media, etc, should be creatively utilized by advertising agencies to create more visibility of products that can help the consumer make better purchasing decisions.